(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract Housekeeping plays an important role in any hospitality setting. This department is tasked with maintaining the hotel’s cleanliness and keeping the hotel in a desirable ambiance. This study determines the overall vitality of the research idea that was originally proposed by the bachelor of science in hospitality management students of Bestlink College of the Philippines. It Emphasizes the capability of the proposed recommendation for the satisfaction of the guests concerning the quality of housekeeping services in McHotel Novaliches, involving the planning to enhance, implement, and change the negative perception of many guests about services in the said hotel. In order for the guests to unwind and enjoy their stay when they are traveling far from home, the housekeepers should keep each guest’s room tidy and organized. The enthusiasm, passion, and commitment of its housekeeping staff are said to be among the motivating aspects for providing high-quality service. By delivering quality service, the department can contribute to establishing and preserving the hotel’s favorable reputation and image. The result shows that guests are satisfied with the quality of housekeeping services in terms of reliability, responsiveness, empathy, assurance, and tangibility. On the other hand, guests or respondents are also satisfied with how the hotel maintained guest loyalty in terms of technology, rooms, amenities, and services. Hotels should always be willing to be involved with trends in terms of providing quality services in order to satisfy guests, and they should constantly strive to improve their services based on guests’ feedback. In order to maintain guest satisfaction, they should measure it regularly and implement programs that offer rewards to loyal guests. Rewarding guests through the created programs is like letting them enhance their experience. They should also invest more in technology because it has a vital contribution to improving guest satisfaction. In order to have easy access, the hotel should upgrade its facilities and include certain modern equipment, and it should improve its front area to attract potential guests.